The Music of Rebellion in the Poems of Rauf Parfi (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article analyzes the rebellious spirit of Rauf Parfi’s poems. It reflects the charm of the poet’s poems, the textual perfection, the harmony of the words with the melody. Poet’s rebellious poems are compared with Cholpan’s poems.